Defence-related components in cucumber susceptibility to target spot - Fischer, Ivan Herman; Morales, João Vitor Pelizzaro; Meleiro Da Silva, Lucas; Cagnin Martins Parisi, Marise; Amorim, Lilian; Pascholati, Sergio Florentino (Comunicata Scientiae, 2023)
Target spot is an important disease in cucumber culture. Due to differences in the susceptibility of cucumber cultivars to the disease, the objective was to evaluate the behavior of three cvs. in terms of leaf trichome density and biochemical variables in the interaction with the pathogen Corynespora cassiicola. The density of trichomes was evaluated on both sides of the leaves. The activity of peroxidase and polyphenol oxidase enzymes and the levels of free and bound phenolic compounds were evaluated one, three and five days after inoculation or not with the pathogen. The enzymatic activity was higher in the Safira cv., less susceptible to the disease, in relation to the Taiko and Soldier cvs. Inoculated plants showed higher peroxidase activity, showing that the response to infection was accompanied by the synthesis of this enzyme, and it increased with the days after inoculation. The levels of phenolic compounds varied according to the cvs. and as a function of time, with the highest levels in the Safira and Soldier cvs. Higher density of trichomes was found in the Safira cv., with no differences between Soldier and Taiko cvs. The adaxial side of the leaves had a greater number of trichomes than the abaxial side. No direct relationships were observed between biochemical and trichome variables and disease severity in cucumber cvs., since the Soldier cv., the most susceptible to the disease, did not differ in relation to ’Taiko’ in enzymatic activities, free phenolic compounds and number of trichomes, including higher levels of bound phenolic compounds.